2022
DOI: 10.3390/psych4010012
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Clinical Strategies for Treatment-Resistant Depression: Integrating Ketamine Protocols with Trauma- and Attachment-Informed Psychotherapy

Abstract: Strategically timed trauma- and attachment-informed psychotherapy to address underlying emotional wounds, paired with ketamine administered in precision-calibrated doses to ensure high-entropy brain states, may be key to improving the quality and duration of ketamine’s therapeutic efficacy for treatment-resistant depression. This approach optimizes the opportunities for change created by ketamine’s known effects as a rapid antidepressant that stimulates synaptogenesis, normalizes neural connectivity and cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…This synergy between acute changes in synaptic gain and sub-acute changes in neural plasticity also suggests that complementing the pharmacological treatment with psychotherapy may have additive benefits. Recently, Muscat et al (2022) proposed an integrative approach that aims to help improving the development of ketamine treatment protocols and clinical outcomes. The authors propose that preparation sessions, which should be based on a psychoeducational-based approach, may allow to increase efficacy and safety as the multiple levels of the beneficial actions of ketamine are extensively discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This synergy between acute changes in synaptic gain and sub-acute changes in neural plasticity also suggests that complementing the pharmacological treatment with psychotherapy may have additive benefits. Recently, Muscat et al (2022) proposed an integrative approach that aims to help improving the development of ketamine treatment protocols and clinical outcomes. The authors propose that preparation sessions, which should be based on a psychoeducational-based approach, may allow to increase efficacy and safety as the multiple levels of the beneficial actions of ketamine are extensively discussed.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published trial of ketamine combined with mindfulness-based relapse prevention for alcohol use disorder demonstrated that treatment with three infusions of ketamine was associated with more days of abstinence from alcohol at 6-month follow-up ( Grabski et al, 2022 ). After reviewing these and other studies, Muscat et al (2022) have recently argued for the potential benefits of integrating ketamine protocols with psychotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the absence of a lasting antidepressant or anti-suicidal impact of ketamine, especially in treatment-resistant populations, calls for strategies to extend these effects beyond repeated administration ( 136 , 137 ). Future research should investigate whether combining psychedelic-assisted therapy with ketamine infusions is necessary for the revision of negative beliefs, the acceptance of emotions, thoughts, and memories, and sustaining therapeutic effects ( 138 , 139 ). Computational models could be used to quantify long-term changes in cognitive processes associated with this combined therapeutic approach.…”
Section: Additional Considerations and Potential Applications Of Comp...mentioning
confidence: 99%
“…However, increased concentrations of inflammatory biomarkers have been found in individuals with depression compared to those without depression. Elevated concentrations of inflammatory markers may indicate a weak antidepressant response [ 8 , 9 ]. However, while approximately half of depressed patients show a sufficient response to antidepressants, around 15% show only a partial response to therapy.…”
Section: Introductionmentioning
confidence: 99%